Inequality and Efficiency - Does a Wider Spread of Wages Raise Employment? - Ronald Schettkat (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2006)
First paragraph: The assumed trade-off between efficiency and equality is deeply engraved in the minds of many economists. Applied to labor markets this assertion says that a wider dispersion of wages raises employment. Welch (1999), addressing the American Economic Association in the Richard T. Ely Lecture, praises the beauty of an economy with high inequality, and sociologists claim that inequality is the price for freedom (Dahrendorf 2006). Why should a wider wage dispersion improve employment? Many hypotheses have been forwarded: wages equal workers' marginal productivity and therefore a wider dispersion of wages allows for an integration of the less productive workers; workers of all ranks are – like tournament players – motivated by the high rewards for the winner, i. e. the top earners; all western economies were hit by the same shocks (skill-biased technological change, globalization), which are disadvantageous for less skilled workers and result in a wider dispersion of wages in countries with flexible wage structures but in unemployment in countries with inflexible wage structures (the two sides of the same coin hypothesis, Krugman 1994). But it is unclear whether declining demand for less skilled workers erodes their wages or whether wage compression extinguishes demand for less skilled labor. Among the first U. S. economists who discussed the rising dispersion of wages were Harrison/Bluestone (1981) who emphasized the changing industry structure (declining manufacturing and rising services) as the major cause for rising wage inequality in America. The industry structure, however, turned out not to be the driving force behind the rising wage inequality in the U. S. The image of services as McDonald jobs was oversimplified since the sector includes also high-paid McKinsey jobs (Freeman / Schettkat 1998). Contrary to common believes, employment growth in the USA was not concentrated in the low skill sector, here demand declined substantially, but rather in higher skills.
Keywords: 330